The Influence of Transformational Leadership and Organizational Fairness on Employee Organizational Commitment: An Empirical Study on Employees - Ahmad Musthofa Zuhad (CV. Civiliza Publishing, 2026)
This study aims to analyze the influence of transformational leadership and organizational justice on organizational commitment. The study used a quantitative approach with a saturated sampling technique, involving 42 respondents from the trucking, operations, finance, driver, and human resource divisions. Data were analyzed using multiple linear regression with SPSS. The results show that organizational justice has a positive and significant effect on organizational commitment (p = 0.002 < 0.05), indicating that the higher employees’ perception of organizational justice, especially in terms of opportunities to participate before important decisions are made, the higher their commitment to the organization. In contrast, transformational leadership does not have a significant effect on organizational commitment (p = 0.069 > 0.05). This finding indicates that the leader’s role as an ethical role model has not been strongly perceived by employees, so transformational leadership has not been able to directly improve organizational commitment. Descriptively, transformational leadership was rated positively with a total mean of 4.439, particularly in the aspect of encouraging employees to express ideas freely, while organizational justice was in the good category with a total mean of 3.89, especially in the aspect of providing opportunities to voice input before important decisions are made. These findings confirm that organizational commitment is more strongly formed when the organization consistently applies fairness in its policies and treatment of employees.